3-Hydroxyflavone inhibits human osteosarcoma U2OS and 143B cells metastasis by affecting EMT and repressing u-PA/MMP-2 via FAK-Src to MEK/ERK and RhoA/MLC2 pathways and reduces 143B tumor growth in vivo. (November 2016) - Lu, Ko-Hsiu; Chen, Pei-Ni; Hsieh, Yi-Hsien; Lin, Chin-Yin; Cheng, Fu-Yuan; Chiu, Peng-Chou; Chu, Shu-Chen; Hsieh, Yih-Shou
Abstract: Many natural flavonoids have cytostatic and apoptotic properties; however, we little know whether the effect of synthetic 3-hydroxyflavone on metastasis and tumor growth of human osteosarcoma. Here, we tested the hypothesis that 3-hydroxyflavone suppresses human osteosarcoma cells metastasis and tumor growth. 3-hydroxyflavone, up to 50 μM without cytotoxicity, inhibited U2OS and 143B cells motility, invasiveness and migration by reducing matrix metalloproteinase (MMP)-2 and urokinase-type plasminogen activator (u-PA) and also impaired cell adhesion to gelatin. 3-hydroxyflavone significantly reduced p-focal adhesion kinase (FAK) Tyr397, p-FAK Tyr925, p-steroid receptor coactivator (Src), p-mitogen/extracellular signal-regulated kinase (MEK)1/2, p-myosin light chain (MLC)2 Ser19, epithelial cell adhesion molecule, Ras homolog gene family (Rho)A and fibronectin expressions. 3-hydroxyflavone also affected the epithelial-mesenchymal transition (EMT) by down-regulating expressions of Vimentin and α-catenin with activation of the transcription factor Slug. In nude mice xenograft model and tail vein injection model showed that 3-hydroxyflavone reduced 143B tumor growth and lung metastasis. 3-hydroxyflavone possesses the anti-metastatic activity of U2OS and 143B cells by affecting EMT and repressing u-PA/MMP-2 via FAK-Src to MEK/ERK and RhoA/MLC2 pathways and suppresses 143B tumor growth in vivo . This may lead to clinical trials of osteosarcoma chemotherapy to confirm the promising result in the future. Graphical abstract: Highlights: 3-Hydroxyflavone inhibits U2OS and 143B cells migration, invasiveness and motility. 3-Hydroxyflavone inhibits MMP-2 of U2OS and 143B cells and u-PA of U2OS cells. 3-Hydroxyflavone decreases FAK, Src, MEK/ERK and MLC2 phosphorylation. 3-Hydroxyflavone affects EMT of U2OS and 143B cells. 3-Hydroxyflavone reduces 143B tumor growth in vivo .